Properties of high-quality hydrolysate prepared from mudskipper (Periophthalmus freycinetii). Issue 1 (May 2020) - Nurdiani, R; Yulia, M R; Prihanto, A A
Abstract: Mudskipper ( Periophthalmus freycinetii ), an amphibious fish, lives in tidal areas and is known for its ability to climb, walk and skip about out of water. It contains high protein and taurine and exhibit unique adaptation to extreme environment. Despite its potential, mudskipper is still underutilized. The aim of this research was to examine the biochemical properties and antioxidant activity of mudskipper hydrolysate. The mudskipper was hydrolyzed using endogenous enzymes under different pH (control, 5, 7, 9) and hydrolysis duration (12 and 24 hours). Hydrolysates were characterized with respect to ash, moisture, fat and protein content as well as the yield and amino acid composition. Antioxidant activity of mudskipper hydrolysate was tested using DPPH. pH 9 and 24h hydrolysis duration gave the highest yields (80.48%), degree of hydrolysis (DH) (37.22%) and protein content (52.63%). High antioxidant activity (56.12%) was also observed. The molecular weight of hydrolysate ranged from 12.55 – 117.73kDa. The hydrolysate contained 35.31% essential amino acid and 63.63% non-essential amino acids which may relate to its functional and bioactive properties. The results suggested that underutilized fish has potency as source of high-quality hydrolysate.